Assessment of Sowing Quality of Radish Seeds with Working Unit of Pneumatic Seeder (Agricultural Engineering, 2017)
The objective of the research was assessment of the sowing quality of radish seeds with the sowing unit of “MAX PNEUAMTIC” S 156 pneumatic seeder. Tests were carried out on the original laboratory stand. They proved that at the assumed range of the working speed within 2.5 to 4.0 km·h−1 and rotations of the sowing disc between 23 and 37 rot·min−1, the most favourable results concerning precision of seeds spacing in a row were obtained at the speed between 2.5 and 3.0 km·h−1. The increase of the speed above 3.0 km·h−1 caused deterioration of the seeds sowing quality through statistically significant reduction of the single sowing participation and the increase of the empty sowings participation.